A key role for the periplasmic PfeE esterase in iron acquisition via the siderophore enterobactin in Pseudomonas aeruginosa - Perraud, Q; Moynié, L; Gasser, V; Munier, M; Godet, J; Hoegy, F; Mély, Y; Mislin, G; Naismith, J; Schalk, I (American Chemical Society, 2018)
Enterobactin (ENT) is a siderophore (iron-chelating compound) produced by Escherichia coli to gain access to iron, an indispensable nutrient for bacterial growth. ENT is used as an exosiderophore by Pseudomonas aeruginosa with transport of ferri-ENT across the outer membrane by the PfeA transporter. Next to the pfeA gene on the chromosome is localized a gene encoding for an esterase, PfeE, whose transcription is regulated, as for pfeA, by the presence of ENT in bacterial environment. Purified PfeE hydrolyzed ferri-ENT into three molecules of 2,3-DHBS (2,3-dihydroxybenzoylserine) still complexed with ferric iron, and complete dissociation of iron from ENT chelating groups was only possible in the presence of both PfeE and an iron reducer, such as DTT. The crystal structure of PfeE and an inactive PfeE mutant complexed with ferri-ENT or a nonhydrolyzable ferri-catechol complex allowed identification of the enzyme binding site and the catalytic triad. Finally, cell fractionation and fluorescence microscopy showed periplasmic localization of PfeE in P. aeruginosa cells. Thus, the molecular mechanism of iron dissociation from ENT in P. aeruginosa differs from that previously described in E. coli. In P. aeruginosa, siderophore hydrolysis occurs in the periplasm, with ENT never reaching the bacterial cytoplasm. In E. coli, ferri-ENT crosses the inner membrane via the ABC transporter FepBCD and ferri-ENT is hydrolyzed by the esterase Fes only once it is in the cytoplasm.